Penerapan Model Problem Based Learning Untuk Mengamati Kemampuan Peserta Didik Pada Pembelajaran Skala di Kelas V SDN 2 Luwung - Hilda Fahira; Jannah Mutiarani Pradana; Tita Aulia (PT. ALHAFI BERKAH INDONESIA, 2023)
This article was created with the aim of describing the results of research on the use of the Problem Based Learning or PBL model in scale learning in class V elementary schools. This research is classroom action research. The subjects taken were class V students of SDN 2 Luwung for the 2022/2023 academic year. Data collection techniques in this research are observation, interviews, documentation and tests. Based on the research results, it can be concluded that the use of the PBL model in class V scale material can take place well and regularly, students can understand the material well and can respond actively to learning when delivering the material.